(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This work analyzes the processes of diagnosis and treatment of liver cirrhosis using modern medical technologies. The study highlights the role of digital medicine, artificial intelligence-based diagnostics, elastography, computed tomography (CT), magnetic resonance imaging (MRI), and bioinformatics approaches in clinical practice. It also examines the importance of modern technologies in early detection of the disease, improving treatment effectiveness, and monitoring patient conditions.